A Flat Lens with Tunable Phase Gradient by Using Random Access Reconfigurable Metamaterial. (16th July 2015) - Zhu, Weiming; Song, Qinghua; Yan, Libin; Zhang, Wu; Wu, Pin‐Chieh; Chin, Lip Ket; Cai, Hong; Tsai, Din Ping; Shen, Zhong Xiang; Deng, Tian Wei; Ting, Sing Kwong; Gu, Yuandong; et al.
<x xml:space="preserve">Abstract</x> The first demonstration of an optofluidic metamaterial is reported where resonant properties of every individual metamolecule can be continuously tuned at will using a microfluidic system. This is called a random‐access reconfigurable metamaterial, which is used to provide the first demonstration of a tunable flat lens with wavefront‐reshaping capabilities.